The Effects of Mathematics Anxiety on Mathematics Performance among Secondary School Students in Tanzania: A Case of Arusha City Council - Salahot, Ester Damiano (International Journal of Scientific Research and Management (IJSRM), 2022)
The continuous trend of poor mathematics performance in Tanzania has developed different stakeholders' attention, including the Government, to research the possible causes of poor performance. The presence of mathematics anxiety among students is believed to have an impact on students' performance in Mathematics. In this study, the researcher aimed to investigate the effects of Mathematics Anxiety on Mathematics Performance Among Secondary Schools Students in Tanzania. The study employed a sample size of 396 students from six secondary schools in the Arusha City Council. The researcher collected data through structured questionnaires with closed-ended questions distributed to respondents. Respondents' mathematics terminal examination marks were used in this study. The collected data were analysed using descriptive (percentages and mean) and inferential statistics (correlation and multiple regression analysis). The results generally revealed a significant effect of mathematics anxiety on mathematics performance among secondary school students at a 0.05 level of significance (P-Value 0.00 2- tailed). A correlation coefficient r = 0.304 indicate a significant moderate positive relationship between the effects of mathematics anxiety and mathematics performance. The regression equation  indicates that mathematics anxiety affects mathematics performance by 46.6% when other factors remain constants. Based on the findings, it was recommended that mathematics teachers be aware of the possibility of mathematics anxiety among their students. Also, further studies that involve a large sample should be conducted to re-confirm the assertion.